2004
DOI: 10.1177/0743558403260021
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Neighborhood Quality on Adolescents’ Educational Values and School Effort

Abstract: Interview data from a sample of 262 poor African American single mothers and their 7th- and 8th-grade children were used to investigate the relations between neighborhood conditions and adolescents’educational values and school effort. The model tested incorporates both subjective and objective assessments of neighborhood quality and controls for several family- and school-related constructs. United States Census data on household incomes served as an objective measure of neighborhood quality. In the full samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 24 publications
1
63
0
2
Order By: Relevance
“…This may have happened because the dimensions of both learning effort models had not been previously empirically analyzed and both conceptualizations had solely been done in light of the literature. However, a review of the related literature proves that many researchers have acknowledged attention and attentiveness as a dimension of effort (Ceballo, McLoyd, & Toyokawa, 2004;Chao, 2001;Cho, 2015;Cowan, 2005;Finn, Lee, Kraus, & Hudson Kam, 2014;Idan & Margalit, 2014;Shouse, Schneider, & Plank, 1992). Moreover, as argued by Kanfer (1992), effort is both physical and cognitive, and as asserted by many scholars, cognitive effort is the load of attention apportioned to a process, learning English in this context.…”
Section: Discussionmentioning
confidence: 99%
“…This may have happened because the dimensions of both learning effort models had not been previously empirically analyzed and both conceptualizations had solely been done in light of the literature. However, a review of the related literature proves that many researchers have acknowledged attention and attentiveness as a dimension of effort (Ceballo, McLoyd, & Toyokawa, 2004;Chao, 2001;Cho, 2015;Cowan, 2005;Finn, Lee, Kraus, & Hudson Kam, 2014;Idan & Margalit, 2014;Shouse, Schneider, & Plank, 1992). Moreover, as argued by Kanfer (1992), effort is both physical and cognitive, and as asserted by many scholars, cognitive effort is the load of attention apportioned to a process, learning English in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Tita et al (2006); Lynch and Rasmussen (2001); Linden and Rockoff (2008) find a negative effect of crime and violence on real estate prices. Bowen and Bowen (1999); Schwartz and Gorman (2003); Ceballo et al (2004) find that exposure to violence in the neighborhood or in-school bullying has detrimental effects on children's perception of security, school attendance and grades.…”
Section: Introductionmentioning
confidence: 99%
“…One of the few studies has revealed that students are more interested in doing activities for which they value and think they have the necessary competence (Ceballo, McLoyd, & Toyokawa, 2004). Students who value new skills established favorable motivational beliefs (Boekaerts, 2002).…”
Section: Values Attached To Education and Educational Motivationmentioning
confidence: 99%
“…Students who value new skills established favorable motivational beliefs (Boekaerts, 2002). According to Ceballo, McLoyd, and Toyokawa (2004), self-perceived academic abilities were significantly linked to adolescents' educational values, which were, in turn, related to school effort. Other researchers observed that students' academic achievement required coordinated interactions between different aspects of motivation (Amrai, Motlagh, Zalani, & Parhon, 2011) and the present study argues that such motivation would be values.…”
Section: Values Attached To Education and Educational Motivationmentioning
confidence: 99%